Emotional Responses of Neonatal Intensive Care Nurses to Neonatal Death. (June 2022) - Köktürk Dalcalı, Berna; Can, Şeyda; Durgun, Hanife
The study was planned as a descriptive qualitative study to determine the emotional responses of neonatal intensive care nurses to work in the neonatal unit and to neonatal deaths. The sample of the study consisted of 7 nurses who work at the neonatal intensive care unit since data saturation was achieved. The data were collected using the "Semi-Structured In-Depth Interview Guide for Nurses". The data were analyzed using the content analysis method. Following codes were reached as a result of the study: 'happiness-sadness', 'professional satisfaction-exhaustion', 'empathy', 'responsibility-guilt', 'hope-despair' under the theme of being a nurse at neonatal unit'; 'unforgettable first loss', 'professionalism in intervention-and then: sadness, 'mature-premature difference', 'difficulty in giving hurtful news-inability to associate with death' and 'attachment-burnout' under the theme of experiencing neonatal loss.It was seen that nurses' emotions about working at neonatal intensive care unit were generally positive; however, these emotions changed to negative after neonate's relapsing and death.